2019
DOI: 10.1177/2066220319862773
|View full text |Cite
|
Sign up to set email alerts
|

The complexities of managing gendered violence in an English probation setting

Abstract: Examined in this article are two cases of women who have committed offences causing serious harm to others. Responses from probation practitioners are explored in the context of the women also being viewed as victims of extreme, long-term abuse and subsequent trauma. Organisational pressures and practitioners’ personal values are analysed to see in what ways interventions attempt to balance individuals’ offending and victimisation aspects, whilst also being mindful of traumatising effects of the criminal justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Consistent with the community correctional literature (Goldhill, 2019;Rhineberger-Dunn et al, 2016;Severson and Pettus-Davis, 2013), the primary operational stressor identified by PPOs was potential secondary trauma arising from exposure to details about the actions or personal histories of those under their supervision and victims. Respondents regularly identified the stress that secondary exposure could cause.…”
Section: Operational Stressors: Exposure To Pptes and Secondary Traumamentioning
confidence: 73%
See 3 more Smart Citations
“…Consistent with the community correctional literature (Goldhill, 2019;Rhineberger-Dunn et al, 2016;Severson and Pettus-Davis, 2013), the primary operational stressor identified by PPOs was potential secondary trauma arising from exposure to details about the actions or personal histories of those under their supervision and victims. Respondents regularly identified the stress that secondary exposure could cause.…”
Section: Operational Stressors: Exposure To Pptes and Secondary Traumamentioning
confidence: 73%
“…Unlike many other public safety personnel, community-based PPOs less frequently (although not rarely) respond directly to PPTEs; however, as part of their ongoing operational duties, PPOs regularly can experience vicarious or secondary trauma as they learn about the histories of those under their supervision ( Goldhill, 2019 ; Rhineberger-Dunn et al, 2016 ; Severson and Pettus-Davis, 2013 ). For example, PPOs speak with clients about their personal histories (which are often traumatic; Goldhill, 2019 ) and criminal offences, reading details about these crimes in reports and victims’ statements, or other documentation.…”
Section: Operational and Organisational Stressors In Public Safety Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, domestic abuse perpetrators may also be perpetrators of sexual violence and child abuse meaning that practitioners may be exposed to multiple stories of harm, trauma, and violence. Vicarious trauma can be particularly problematic for new staff (Lee, 2017a) while probation practitioners who have had their own encounters with trauma may become re-traumatised (Cluley and Marston, 2018; Goldhill, 2019).…”
Section: The Emotional Impact Of Working With Serious Violent Offendersmentioning
confidence: 99%